Understanding social engagement in autism: being different in perceiving and sharing affordances - Hellendoorn, Annika (Frontiers in Psychology, 2014)
In the current paper I will argue that the notion of affordances offers an alternative to theory of mind (ToM) approaches in studying social engagement in general and in explaining social engagement in autism spectrum disorder (ASD) specifically. Affordances are the possibilities for action offered by the environment. In contrast to ToM approaches, the concept of affordances implies the complementarity of person and environment and rejects the dualism of mind and behaviour. In line with the Gibsonian idea that a child must eventually perceive the affordances of the environment for others as well for herself in order to become socialized, I will hypothesize that individuals with ASD often do not perceive the same affordances in the environment as other people do and have difficulties perceiving others' affordances. This can lead to a disruption of interpersonal behaviours. I will further argue that the methods for studying social engagement should be adapted if we want to take interaction into account.